Non-invasive Transcranial Electrical Stimulation in Movement Disorders - Ganguly, Jacky; Murgai, Aditya; Sharma, Soumya; Aur, Dorian; Jog, Mandar (Frontiers in Neuroscience, 2020)
Dysfunction within large scale brain networks as the basis for movement disorders is an accepted hypothesis. Treatment options for restoring network function are limited. Non-invasive brain stimulation (NIBS) techniques such as repetitive transcranial magnetic stimulation (rTMS) are now being studied to modify the network. Transcranial electrical stimulation (tES) is also a portable, cost-effective non-invasive way of network modulation. Transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS) have been studied in Parkinson’s disease, dystonia, tremor and ataxia. Transcranial pulsed current stimulation (tPCS) and transcranial random noise stimulation (tRNS) are not yet studied enough. The literature in the use of these techniques is intriguing, yet many unanswered questions remain. In this review we highlight the studies using these four potential tES techniques, their electrophysiological basis, and consider the therapeutic implication in the field of movement disorders. The objective is to consolidate the current literature, demonstrate that these methods are feasible and encourage the application of such techniques in the near future.